Physico-chemical, malting and biochemical properties of some improved Nigerian barley cultivars and their malts - Makeri, Mohammad Usman; Nkama, Iro; Badau, Mamudu Halidu (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Five improved Nigerian barley cultivars (ESCOBA, ASE-2, ALOE, GOB-2, SUMBARD) were obtained from Lake Chad Research Institute Maiduguri, Nigeria, and their physicochemical, malting and biochemical properties investigated employing standard procedures. Data were analyzed by means of ANOVA [at 95% significant level] and correlations using SPSS 14 software. Results showed GOB-2 grain and malt recording the highest kernel weight (47.50 g) and kernel volume (41.21 ml); whereas ALOE grain had the longest kernel length (13.40 mm) and GOB-2 the shortest (9.40 mm). GOB-2 had the largest major diameter (3.39 mm) and SUMBARD had the least (2.86 mm). ESCOBA, SUMBARD and ASE-2 cultivars had the highest protein values (as %N) of 14.90%, 13.90% and 13.69% respectively, while ALOE, ASE-2 and GOB-2had the highest total carbohydrates of 69.97, 69.39 and 68.90% respectively. All the cultivars had good germinative capacities (> 90%), with GOB-2 and ASE-2 having the highest germinative energy values of 96.65% and 95.00%. No significant (p > 0.05) changes in the dimension of the kernels after malting. SUMBARD recorded the highest malt yields (88.55%)followed by ASE-2 (83.45%) and ALOE (82.00%). The highest α-amylase activities of 105.34 and 96.23 unit/mg protein/min were recorded by ASE-2 and ALOE, respectively, with corresponding diastatic powers of 81.92 and 76.23oL. Thousand kernel weight correlated positivelywith protein (r = 0.500, P < 0.05) and with total soluble solids (r = 0.435, p < 0.05) but negatively with α-amylase (r = -0.869, p < 0.05) and with diastatic power (r = -0.838, p < 0.05). This study showed that the cultivars have good potentials for use as malting materials in beverage making.